A precise microwave spectroscopy measurement on the muonium ground state: hyperfine structure interval and muon magnetic moment - Boshier, Malcolm G.; Jungmann, Klaus; Prigl, Ralf; Putlitz, Gisbert zu; Reinhard, Irene (1996 Conference on Precision Electromagnetic Measurements digest, 1996)
An experiment is in progress at the Los Alamos Meson Physics Facility (LAMPF) to determine with high precision the hyperfine structure interval /spl Delta/v (to /spl sim/10 ppb) and the muon to proton magnetic moment ratio /spl mu//sub /spl mu////spl mu//sub p/(to /spl sim/60 ppb) in the ground state of muonium (/spl mu//sup +/e/sup -/). These precision goals correspond to increases in precision of /spl Delta/v and of /spl mu//sub /spl mu////spl mu//sub p/ by about a factor of 5 compared to present knowledge.